Diagnóstico y tratamiento artroscópico de la luxación aguda del hombro - Ontaneda Vásquez, Irma Bianca (Machala : Universidad Técnica de Machala, 2021)
INTRODUCTION: Glenohumeral dislocation is one of the orthopedic disorders that occurs most frequently in young athletes, causing a capsulolabral injury in them, which may or may not compromise bone tissue and result in medium-term recurrences. (1)(2) Over time, various surgical procedures have been proposed to correct and stabilize the glenohumeral joint, however, at present the arthroscopic technique is considered the surgical treatment of choice. (2) MATERIALS AND METHODS: An exhaustive bibliographic review of scientific articles published with evidence-based medicine and high-impact journals in Pubmed, Cochraine, Scielo, within the last 5 years was carried out. For which the term shoulder instability, arthroscopy, diagnosis, treatment and shoulder dislocation was used. In addition, a descriptive and explanatory methodology was used based on all the information collected from the scientific articles. OBJECTIVE: To analyze the arthroscopic diagnosis and treatment of acute shoulder dislocation, by reviewing scientific articles. CONCLUSION: The use of arthroscopy as a surgical treatment in glenohumeral dislocation consists of better results such as a shorter hospital stay, lower risk of instability, in addition to the majority of the intervened people have resumed their sports activities in approximately 2 years, but of these not all people have the same sporting level that they presented before. Complications were also minor in relation to open surgery. KEY WORDS: Shoulder dislocation, shoulder instability, arthroscopy, diagnosis, treatment.
INTRODUCCIÓN: La luxación glenohumeral es uno de los trastornos ortopédicos que se presentan con mayor frecuencia en atletas jóvenes, provocando en ellos una lesión capsulolabral, la cual puede comprometer o no el tejido óseo y dar como consecuencia recurrencias a mediano plazo. (1)(2) A lo largo del tiempo se han propuesto varios procedimientos quirúrgicos para corregir y estabilizar la articulación glenohumeral, sin embargo, en la actualidad la técnica artroscópica es considerada como el tratamiento quirúrgico de elección. (2) MATERIALES Y MÉTODOS: Se realizó una revisión bibliográfica exhaustiva de artículos científicos publicados con medicina basada en evidencia y revistas de alto impacto en Pubmed, Cochraine, Scielo, dentro de los últimos 5 años. Para lo cual se utilizó la terminología inestabilidad del hombro, artroscopía, diagnóstico, tratamiento y luxación de hombro. Además, se usó una metodología descriptiva y explicativa basada en toda la información recolectada de los artículos científicos. OBJETIVO: Analizar el diagnóstico y tratamiento artroscópico de la luxación aguda de hombro, mediante la revisión de artículos científicos. CONCLUSIÓN: El uso de la artroscopía como tratamiento quirúrgico en la luxacion glenohumeral consta de mejores resultados como una menor estancia hospitalaria, menor riesgo de inestabilidad, además la mayoría de las personas intervenidas refieren haber retomado sus actividades deportivas en aproximadamente 2 años, pero de estas personas no todas tienen el mismo nivel deportivo que presentaban antes. PALABRAS CLAVE: Luxación de hombro, inestabilidad del hombro, artroscopía, diagnóstico, tratamiento.
Keywords: LUXACION DE HOMBRO; INESTABILIDAD DEL HOMBRO; ARTROSCOPIA; DIAGNOSTICO